Pasts of Determinism: A Note on (Ian) Hacking. - Tasić, Vladimir (Parallax)
The determinism of our fictional world of new science may not have been of the old Laplacian variety (now perceived as naive, linear, inadequate for our complex and unpredictable world), but it was still determinism. I But we should not forget the darker side of unreason that underlies the fragmentation of old concepts and their replacement by new ones. i [1] Ian Hacking Introduction There are different kinds of determinism. Hacking describes it, with characteristic depth of insight and affinity for memorable turns of phrase, as a "silly season for determinism culminating about 1872".[7] It was a period marked by "zany intellectual ferment" and 'a whole series of conceptual confusions, false starts and crazy responses' that resulted in 'a wide-ranging intellectual mutation to which the erosion of determinism is central.'[8] Hacking remains within the nineteenth century timeframe in his far more detailed study, I The Taming of Chance i (1990), which shows how the conceptual disturbances related to determinism gave rise to a probabilistic or statistical turn.